Progression of Baseline Electrocardiogram Abnormalities in Chagas Patients Undergoing Antitrypanosomal Treatment. (19th January 2019) - Soverow, Jonathan; Hernandez, Salvador; Sanchez, Daniel; Forsyth, Colin; Flores, Carmen A; Viana, Gracia; Meymandi, Sheba
Abstract: Background: The objective of the study was to better understand the impact of antitrypanosomal treatment on the evolution of Chagas-related, prognostically important electrocardiogram (ECG) abnormalities. Methods: Initial and posttreatment ECGs were obtained in a prospective cohort of Chagas patients treated with nifurtimox or benznidazole and compared to an untreated cohort. Electrocardiogram disease progression was compared in those with and without baseline abnormalities pre- and posttherapy. Results: Fifty-nine patients were recruited in the treatment arm and followed for an average of 3.9 years. There were no differences between ECG groups with regards to follow-up, age, baseline ejection fraction, or therapy. In the treated cohort, 0 of 30 patients with normal ECGs developed an abnormal ECG compared with 7 of 29 patients with baseline ECG abnormalities who developed new ECG abnormalities ( P = .005). In an untreated cohort of 30 patients, 3 of 7 with normal ECGs developed an abnormality compared with 14 of 23 patients with baseline abnormalities ( P = .67). Untreated patients had a higher likelihood of developing new EKG abnormalities (56.7% vs 11.9%, P < .001) despite shorter follow-up, and in a multivariate analysis adjusting for baseline EKG status across both treated and untreated cohorts, treated patients were still less likely to have progression of their EKG disease (odds ratio = 0.13, P < .001). The corrected QT (QTc) interval was not significantly affected by either study medication (415 vs 421 ms, initial vs posttreatment QTc; P = .06). Conclusions: Over an average follow-up of 3.9 years, treated patients with normal baseline ECGs did not have significant changes during a course of treatment; however, those with baseline abnormal ECGs had significant progression of their conduction system disease despite treatment, and those without treatment also experienced a progression of ECG disease. These preliminary results suggest that Chagas patients with normal ejection fraction and normal ECG may benefit the most from antitrypanosomal treatment. Abstract : In this study, we describe the evolution of electrocardiogram (ECG) changes in a contemporary United States-based cohort of treated patients, and we suggest that patients who already have prognostically important baseline ECG abnormalities will have continued progression of their conduction system disease despite antitrypanosomal pharmacotherapy.